Correlations Between Serum Cholesterol and Vascular Lesions in Fabry Disease Patients - Katsuta, Hiroki; Tsuboi, Kazuya; Yamamoto, Hiroshi; Goto, Hiromi (Circulation Journal, 2018)
Background: Fabry disease is an X-linked lysosomal storage disorder and shows globotriosylceramide (Gb3) accumulation in multiple organs, resulting from a deficiency of α-galactosidase. In patients with Fabry disease, cardiovascular disease occurs at an early age. Previous studies have shown that serum levels of high-density lipoprotein-cholesterol (HDL-C) increase in this disease, yet its clinical significance for cardiovascular disease remains unclear. Methods and Results: In order to determine why the serum HDL-cholesterol is high in various cardiovascular diseases of Fabry disease patients, we evaluated the serum lipid profiles, ocular vascular lesions, and levels of serum vascular endothelial growth factor (VEGF) and intercellular adhesion molecule-1 in 69 patients with Fabry disease diagnosed by genetic examination. The serum HDL-C/total cholesterol (T-Chol) ratio was significantly high, especially in male patients (41.5±1.7%) regardless of body mass index. Ocular vascular lesions were more likely to occur in female patients with a high HDL-C/T-Chol ratio compared with most male patients. Female patients with a high HDL-C/T-Chol ratio also presented a high serum VEGF level, suggesting that vascular endothelium dysfunction and arteriosclerotic changes progress more severely than in patients with a normal HDL-C/T-Chol ratio. In most patients, enzyme replacement therapy improved serum Gb3 and lyso-Gb3 levels, but these Gb3 and lyso-Gb3 still remained higher than in healthy controls, which appears to result in continuous vascular arteriosclerotic changes. Conclusions: We concluded that increased low-density lipoprotein-cholesterol uptake to the vascular wall caused by endothelial dysfunction is likely to contribute to the high HDL-C/T-Chol ratio observed in Fabry disease patients.